The potential of seaweed cultivation to achieve carbon neutrality and mitigate deoxygenation and eutrophication. (30th December 2021) - Gao, Guang; Gao, Lin; Jiang, Meijia; Jian, Ao; He, Linwen
Abstract: Carbon neutrality has been proposed due to the increasing concerns about the consequences of rising atmospheric CO2 . Previous studies overlooked the role of lost particle organic carbon (POC) and excreted dissolved organic carbon (DOC) from seaweed cultivation in carbon sequestration, that is to say, long term carbon storage in the oceanic sediments and in the water. This study assessed the potential of seaweed cultivation to achieve carbon neutrality of China by 2060 using a new method that included lost POC and excreted DOC. Based on the seaweed production in the years 2015–2019 in China, harvested seaweed removed 605 830 tonnes of carbon, 70 615 tonnes of nitrogen and 8 515 tonnes of phosphorus from seawaters annually; farmed seaweed sequestrated 344 128 tonnes of carbon and generated 2533 221 tonnes of oxygen annually. Among the seven farmed seaweeds, Gracilariopsis lemaneiformis has the highest capacities for carbon removal (9.58 tonnes ha −1 yr −1 ) and sequestration (5.44 tonnes ha −1 yr −1 ) and thus has the smallest cultivation area required to sequestrate 2.5 Gt CO2 that is annually required to achieve China's carbon neutrality goal by 2060. The O2 generated by seaweed cultivation could increase dissolved oxygen in seawaters (0–3 m deep) by 21% daily with gas exchange excluded, which could effectively counteract deoxygenation in seawaters. Gracilariopsis lemaneiformis also has the highest N removal capacity while Saccharina japonica has the highest P removal capacity. To completely absorb the N and P released from the fish mariculture, a production level or a cultivation area two and three times larger (assuming productivity remains unchanged) would be required. This study indicates that seaweed cultivation could play an important role in achieving carbon neutrality and mitigating deoxygenation and eutrophication in seawaters. Cultivation cost could be offset to some extent by increased sales of the harvest parts of the seaweed for food and biofuel.